2020
DOI: 10.3390/plants9101279
|View full text |Cite
|
Sign up to set email alerts
|

Achene Morphology and Anatomy of Clematis L. (Ranunculaceae) in Korea and Its Taxonomic Implications

Abstract: Clematis, a widely distributed genus in Ranunculaceae, is one of the most difficult groups of taxa in the family from a taxonomic point of view. A comprehensive study on achene morphology and the anatomy of 19 taxa of Clematis from Korea was carried out using scanning electron and light microscopy to evaluate the taxonomic significance of achene characters. Clematis achenes are elliptical, obovate or fusiform in shape, light yellow or brown to black in color and completely or sparsely covered with hairs. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Notably,petiole features alone can be more useful for species delimitation than for distinguishing infrageneric relationships and thus are not indicative of infrageneric classifications. Similar explanations were provided by Ghimire et al (2020) and Xie & Li (2012) based on the achene morphology and pollen morphology of Clematis , respectively.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Notably,petiole features alone can be more useful for species delimitation than for distinguishing infrageneric relationships and thus are not indicative of infrageneric classifications. Similar explanations were provided by Ghimire et al (2020) and Xie & Li (2012) based on the achene morphology and pollen morphology of Clematis , respectively.…”
Section: Discussionsupporting
confidence: 64%
“…However, in this study, it remained connected to the Viorna and Atragene sections. In fact, this uncertainty is a common and typical interpretation for this large genus, as previous morphological and molecular studies also found a similar tendency ( Grey-Wilson, 2000 ; Wang & Li, 2005 ; Miikeda et al, 2006 ; Xie, Wen & Li, 2011 ; Xie & Li, 2012 ; Lehtonen, Christenhusz & Falck, 2016 ; Ghimire et al, 2020 ).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations